Chromosome‐Level Genome Assembly and Whole‐Genome Resequencing Revealed Contrasting Population Genetic Differentiation of Black Bream (Megalobrama skolkovii) (Teleostei: Cyprinidae) Allopatric and Sympatric to Its Kin Species - Ruijin Ding; Dan Yu; Ke Yang; Xinghua Wu; Huanzhang Liu (Ecology and Evolution)
ABSTRACT The black bream (Megalobrama skolkovii) is an economically important species widely distributed in China, with its geographic populations potentially having undergone differentiations and local adaptations. In this study, we presented a chromosome‐level genome assembly of this species and investigated genetic differentiations of its populations that are allopatric (the northern one) and sympatric (the Poyang Lake) to its kin species, the blunt‐snout bream (M. amblycephala), using whole genome resequencing analysis. The results showed that the genome size of black bream was 1.13 Gb, very similar to its kin species but larger than its close relatives, the four Chinese major carps. By resequencing individuals from the northern and Poyang Lake populations, we found that the northern population showed lower genetic diversity, larger genetic differentiation, and two sharp historical declines in population size through demographic analysis, indicating the possible bottlenecks after the allopatric isolation. In contrast, the Poyang Lake population, with its higher genetic diversity, higher Tajima's D value, and lower levels of linkage disequilibrium, reflects the ancestral state of black bream. In addition, we also found that the northern population shared more alleles with its kin species, indicating it may retain more ancestral variations. This was further analyzed to be caused by incomplete lineage sorting and ancient introgression. Some key genes related to reproductive processes, body size development, and muscle metabolism were found under selection in the northern population, possibly responsible for its local adaptation. Our findings that the black bream allopatric population had a loss of genetic diversity but retained more ancestral variations can expand our knowledge on population genetic differentiation and give us hints for future genetic conservation.